Nanoformulated paclitaxel and AZD9291 synergistically eradicate non-small-cell lung cancers in vivo. (6th June 2018) - Wang, Xin-shuai; Zhang, Li; Li, Xiaocen; Kong, De-jiu; Hu, Xiao-chen; Ding, Xue-zhen; Yang, Jun-qiang; Zhao, Meng-qi; He, Yixuan; Lam, Kit S; Gao, She-gan; Lin, Tzu-yin; et al.
Aim: This study aims to develop new nanoformulations of EGFR T790M targeted inhibitor AZD9291 and paclitaxel (PTX) for combination therapy of lung cancer.Materials & methods: We prepared and characterized PTX- and AZD9291-loaded disulfide cross-linking micelles (DCMs), and evaluate their combination effect and toxicity in vitro and in lung cancer-bearing mice.Results: Drug-loaded DCMs were relatively small in size, and possessed glutathione-responsive drug release. The combination of PTX–DCMs and AZD92921–DCMs exhibited strong synergistic effects in both cell line and in vivo without additional toxicity. Molecular studies demonstrated the synergistic modification in both IKB-α/NF-κB/Bcl-2 and EGFR/Akt pathways.Conclusion: The combination of DCM-loaded AZD9291 and PTX could potentially offer more effective and less toxicity treatment options for lung cancer patients.